Long-term benefits of exercising on quality of life and fatigue in multiple sclerosis patients with mild disability: a pilot study - McCullagh, Ruth; Fitzgerald, Anthony P; Murphy, Raymond P; Cooke, Grace (Clinical rehabilitation, 2008)
Objective: To determine if exercise benefits patients with multiple sclerosis. Design: Randomized controlled trial. Settings: Participants exercised at home and also attended exercise classes held in a hospital physiotherapy gym. Subjects: Thirty patients, diagnosed and independently mobile, were recruited in the Dublin area. Intervention: For three months, classes were held twice-weekly and participants exercised independently once-weekly. The control group was monitored monthly and management remained unchanged. Measurements: Measurements were taken at baseline, three and six months. The Modified Fatigue Impact Scale (MFIS), Multiple Sclerosis Impact Scale-29 (MSIS-29) and Functional Assessment of Multiple Sclerosis (FAMS) were used to measure fatigue and quality of life (QOL). Heart rate (HR) and the Borg's Rating of Perceived Exertion (RPE) were recorded during an incremental exercise test. The change from baseline scores between groups was compared using the Mann—Whitney U-test. Results: Twenty-four participants completed the programme (n = 12 in each group). Based on the change in scores at three months, the exercise group had significantly greater improvements in exercise capacity (HR: —14 [-18.5, -2.5] versus 0.5 [-4, 5.5], P= 0.009), QOL (FAMS: 23 [9.5, 42.5] versus -3.5 [-16, 5], P=0.006) and fatigue (MFIS: -13 [-20, -3] versus 1 [-4, 4.5], P=0.02). At six months, the difference in change scores remained significant for FAMS (19 [14, 31] versus -4.5 [-25, 8], P=0.002) and MFIS (-8.5 [-19.5, -1] versus 0.5 [-2.5, 6.5], P=0.02) only. Conclusions: A three-month exercise programme improved participants' exercise capacity, QOL and fatigue, with the improvements in QOL and fatigue lasting beyond the programme.